Peran Nilai yang dirasakan dan Kualitas Layanan terhadap Loyalitas Pelanggan di Laundry the Daily Wash - Nur Fadilah Tomu; Yulinda L Ismail (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
The purpose of this study was to determine the effect of perceived value on customer loyalty, the effect of service quality on customer loyalty, and the effect of perceived value and service quality simultaneously on customer loyalty at The Daily Wash Laundromat Laundry, H.B. Jassin Branch, Gorontalo. This study used a quantitative approach with an associative research type. The study population included customers who had used The Daily Wash Laundry services more than once. The sample was determined through a purposive sampling technique with the Slovin formula, resulting in 99 respondents. Data were analyzed using SPSS version 27. The results showed that perceived value had a positive and significant effect on customer loyalty with a t-count value of 2.156 > from t-table 1.984. Service quality also had a positive and significant effect on customer loyalty with a t-count value of 5.934 > from t-table 1.984. In addition, perceived value and service quality simultaneously had a positive and significant effect on customer loyalty with an f-count value of 74.325 > from f-table 3.09. These findings indicate that increasing perceived value and service quality plays an important role in forming and maintaining customer loyalty in modern laundry businesses.